The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-34657-4
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Control Trial Of Anti-Inflammatory Regional Hypothermia On Urinary Continence During Robot-Assisted Radical Prostatectomy

Abstract: The present study seeks to present a single-blind, randomized control trial of a hypothermic anti-inflammatory device, the endorectal cooling balloon (ECB), to assess whether regional hypothermia could improve 90-day and time to pad-free continence following robot-assisted radical prostatectomy (RARP). Five high-volume surgeons at three institutions had patients randomized (1:1) to regional hypothermia with ECB versus control. Patients were blinded to device use, as it was inserted and removed intraoperatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…A Swedish population‐based study looking at the effects of surgeon’s ( n = 9) variability on oncological and functional outcomes, also reported large heterogeneity in continence rate after RRP, but not for ED or recurrence rate [16]. In 2018, Huynh et al [24] showed a 10‐fold variation in 3‐month continence rate when comparing five surgeons. Surgeon volume as an important factor for outcomes after RP was first described by Begg et al [23] and has been commented on in follow‐up papers [25] and in subsequent studies on learning curve [21,26–29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Swedish population‐based study looking at the effects of surgeon’s ( n = 9) variability on oncological and functional outcomes, also reported large heterogeneity in continence rate after RRP, but not for ED or recurrence rate [16]. In 2018, Huynh et al [24] showed a 10‐fold variation in 3‐month continence rate when comparing five surgeons. Surgeon volume as an important factor for outcomes after RP was first described by Begg et al [23] and has been commented on in follow‐up papers [25] and in subsequent studies on learning curve [21,26–29].…”
Section: Discussionmentioning
confidence: 99%
“…While heterogeneity in functional and oncological outcomes has been described earlier [15][16][17][22][23][24], underlying factors explaining such heterogeneity have not been reported in detail for RALP or RRP. In 2010, Bianco et al [17] described variations among experienced surgeons in cancer control after RRP in a study from four high-volume centres.…”
Section: Discussionmentioning
confidence: 99%
“…, the authors investigated the effect of regional hypothermia during RALP on urinary continence rates. In their RCT, they compared two parallel groups, finding no benefit in the 3-month continence rates in the regional hypothermia group reporting post-RALP continence of 50% and 59.6% in the regional hypothermia ( n = 100) and control groups ( n = 99) respectively ( p = 0.1748) [ 23 ]. Antonelli et al .…”
Section: Resultsmentioning
confidence: 99%
“…In a unique study by Hyunh et al . , regional hypothermia was trialled as part of the RALP operation via an endorectal cooling balloon, but the technique failed to demonstrate any benefit in return urinary continence [ 23 ]. Delayed versus standard ligation of the dorsal venous complex was studied by Antonelli et al .…”
Section: Discussionmentioning
confidence: 99%
“…Other attempts have been made to reduce post-surgical inflammation after RARP. Some studies evaluated the induction of regional hypothermia via an endorectal cooling balloon; however, a recent randomized control trial demonstrated no significant benefit for continence recovery [58]. In addition, other studies have assessed the use of dehydrated AM tissue around the NVB in accelerating return to potency; however, only one study has reported continence outcomes [41].…”
Section: Discussionmentioning
confidence: 99%